Active in Old Age: Validation and Usability of a Mobile Application for the Academia da Cidade e Saúde Program - Feitosa Lopes, Laryssa Grazielle; da Silva Sobrinho, Andressa Crystine; da Silva Rodrigues, Guilherme; Henrique Sousa-de Araújo, Renatha; de Lima Silva, Aldair; Souza Marques, Maria Júlia; Florencio Da Silva, Jackson Raniel; Bueno Júnior, Carlos Roberto (Universidad y Salud, 2024)
Introduction: Aging, when associated with poor quality of life, contributes to the development of Non-Communicable Diseases (NCDs). NCDs are among the leading causes of mortality worldwide. Objective: To validate the content and usability of the "Active in Old Age" app for professionals and users of the Academia da Cidade e Saúde/Academia da Saúde Program (PACID/PAS). Materials and Methods: An exploratory study conducted between March 2021 and January 2022 in four gyms from a city in the interior of Pernambuco, Brazil. The study included ten users (aged 60 years or older), ten professionals, and ten evaluators. The SUS, SAM, and CVI instruments were used for validation. Results: The overall SAM score was 87.04%, categorizing the material as superior. All items achieved a CVI ≥ 0.80, with a global average CVI of 0.94. Usability scores were 76.75% for users and 84.5% for professionals. Conclusion: The "Active in Old Age" app demonstrated satisfactory parameters for usability and content validity, making it suitable for use in PACID/PAS.